Critical predictors of heart transplant necessity in children with advanced DCM - Zubo Wu; Jiawei Shi; Hui Huang; Jie Liu; Qing Guo; Nianguo Dong; Jing Zhang; Wangzi Li; Lin Wang; Hua Peng (Italian Journal of Pediatrics)
Abstract Background Dilated Cardiomyopathy (DCM) frequently culminates in Heart Failure (HF), positioning it as the primary instigator of cardiac transplantation among pediatric patients. Nevertheless, the issue of cardiac transplantation in children demands a comprehensive and judicious strategy. The aim of this research was to ascertain the clinical attributes at the point of diagnosis that could potentially signal the requirement for transplantation in pediatric patients diagnosed with Dilated Cardiomyopathy (DCM). Methods In our study, we recognized 99 instances of pediatric cardiomyopathy accompanied by advanced heart failure (EF < 30%). The patients were categorized into two cohorts, namely, the transplantation group and the non-transplantation group, based on whether they underwent cardiac transplantation. Each patient in both groups was administered conventional medication. Patients within the non-transplantation group demonstrated improved cardiac function following a minimum of six months of medication therapy. The identification of factors associated with heart transplantation in pediatric DCM was facilitated through the utilization of competing risks and multivariable modeling. Result Out of a total of 99 children, 35 were recipients of transplants, henceforth referred to as the transplantation group, while the remaining 64, diagnosed with Dilated Cardiomyopathy (DCM), did not undergo transplantation, forming the non-transplantation group. A comparative analysis revealed no significant differences in age, gender, and weight between the two groups. However, the transplantation group demonstrated a significantly higher New York Heart Association (NYHA) class 4, incidence of galloping rhythm, hepatomegaly, morphological changes, ascites, and orthopnea in comparison to the non-transplantation group (all p < 0.05).In the meantime, there was a significantly higher incidence of abnormal left ventricular end-diastolic diameter, aortic and pulmonary valve regurgitation rates, and incomplete myocardial compaction in the left ventricle within the transplant group as compared to the non-transplant group (p < 0.05).Nonetheless, the analysis revealed no significant disparities in biochemical markers, which include BNP, CK-MB, CTnI, GOT, BUN, sCr, and GPT, between the two groups (all p > 0.05). A univariate logistic regression analysis demonstrated that NYHA score [aOR (95%CI) = 2.78 (1.06–7.27), p = 0.037], Ascites [aOR (95%CI) = 12.93 (2.45–68.22), p = 0.003], and Left ventricular noncompaction [aOR (95%CI) = 3.73 (1.01–13.86), p = 0.048] were all significantly correlated with the Transplantation group. Conclusions Pediatric dilated cardiomyopathy (DCM) presenting with indicators of progressive heart failure, including an elevated New York Heart Association (NYHA) classification, ascites, and left ventricular non-compaction, necessitates increased vigilance. It is advised that these cases be closely monitored, and early consideration should be given to heart transplantation as a potential therapeutic intervention.